2018
DOI: 10.5603/pjnns.a2018.0003
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of traumatic brain injury: the prognostic accuracy of various scores and models

Abstract: Introduction. Traumatic Brain Injury (TBI) is a worldwide health problem, and is a pathology that causes significant mortality and disability in Latin America. Different scores and prognostic models have been developed in order to predict the neurologi-cal outcomes of patients. We aimed to test the prognostic accuracy of the Marshall CT classification system, the Rotterdam CT scoring system, and the IMPACT and CRASH models, in predicting 6-month mortality and 6-month unfavourable outcomes in a cohort of trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 23 publications
(32 reference statements)
2
14
0
Order By: Relevance
“…Majdan et al compared ROC AUC for the predictive value of Rotterdam and Marshall score and reported similar performance for the two scores. 22 Similar results were found in another study by Charry et al 18 Mata-Mbemba et al reported that Marshall score has as good predictive power as Rotterdam score. 7 Although Mata-Mbemba et al included a large number of patients, their study has high risk of bias due to concealment of allocation.…”
Section: Predictive Value Of the Marshall Ct Scoring Systemsupporting
confidence: 80%
“…Majdan et al compared ROC AUC for the predictive value of Rotterdam and Marshall score and reported similar performance for the two scores. 22 Similar results were found in another study by Charry et al 18 Mata-Mbemba et al reported that Marshall score has as good predictive power as Rotterdam score. 7 Although Mata-Mbemba et al included a large number of patients, their study has high risk of bias due to concealment of allocation.…”
Section: Predictive Value Of the Marshall Ct Scoring Systemsupporting
confidence: 80%
“…These prognostic features have been displayed graphically, enabling risk stratification in relation to outcome, and ultimately, provide a tool to aid in clinical decision making [8,9]. The CRASH and IMPACT models are continuously validated on new patient series [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Charry et al made use of Marshall classification, Rotterdam CT score, IMPACT and CRASH models in its evaluation. They compared all these prognostic tools and found that IMPACT model showed more accuracy than the other prognostic models and had higher sensitivity in predicting a 6-month mortality and 6-month unfavorable outcomes in patients with TBI [16,17]. Khaki et al agreed that Rotterdam CT score is a good prognostic tool and in their study they compared multiple prognostic models (Marshall classification, Rotterdam scoring system, Helsinki CT score and Stockholm CT score) and found Stockholm CT score with the overall strongest relationship when adding variables from the IMPACT base model.…”
Section: Discussionmentioning
confidence: 99%